Association of tuberculosis with vasculitis retinae - Habibullah, M; Uddin, MS; Islam, S (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):129-33. The abstract of this article is available on the PubMed website